Influence of Gelation on the Retention of Purple Cactus Pear Extract in Microencapsulated Double Emulsions - Osorio-Lira, F; Silva-Weiss, A; Santander-Meyer, R; Gimenez-Castillo, B (Public Library of Science, 2020)
A purple cactus pear (Opuntia ficus-indica) extract (CP) was encapsulated in double emulsions (DE) gelled with gelatin (DE-CP-G) and with gelatin and transglutaminase (DE-CP-GT), as well as in a DE with a liquid external aqueous phase (DE-CP), in order to study the retention of betanin as colorant agent. Both gelled DEs showed a predominantly elastic behavior, in contrast with DE-CP. The degradation rate constant of betanin was significantly higher in DE-CP-GT (90.2 x 10−3 days-1) than in DE-CP-G (11.0 x 10−3 days-1) and DE-CP (14.6 x 10−3 days-1) during cold-storage (4 ◦C). A shift towards yellow color was found in all the systems during cold-storage (4 ◦C) and after thermal treatment (70◦C/30 min), especially in DE-CP-GT, denoting a higher degradation of betanin. Betalamic acid, cyclo-Dopa 5-O-β-glucoside, 17-decarboxy-betanin and neobetanin were identified by UHPLC-MS/MS as degradation products of betanin. © 2020 Robert et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.